Peran Manajemen Dakwah dalam Meningkatkan Daya Tarik Masyarakat untuk Beribadah dan Berwisata di Masjid Muhammad Cheng Ho Palembang - Charles Oktriensah (ScidacPlus, 2024)
This study aims to determine the role of da'wah management in increasing public attraction to worship and travel at the Muhammad Cheng Ho Mosque and determine the supporting and inhibiting factors of da'wah management at the Muhammad Cheng Ho Mosque. The object of study was the Muhammad Cheng Ho Mosque. In this study using qualitative descriptive approach method. Data sources and types use primary data and secondary data. The data analysis technique used is descriptive, namely by data collection methods through interviews, observation, and documentation. Data processing techniques in this study include data reduction, data presentation, comparative analysis and conclusions. The results of this study obtained information that the role of da'wah management used by the Muhammad Cheng Ho Mosque includes: planning, compiling and specific briefing. And there are supporting factors of da'wah management in increasing the attractiveness of the community to worship and travel at the Muhammad Cheng Ho Mosque.